Global MPPT Control of Photovoltaic Array Using SEPIC Converter under Partial Shading Condition - J.Senthilnathan (Journal of Power Electronics and Devices, 2019)
The factors affecting the performance characteristics of a photovoltaic (PV) array are temperature, solar insolation, shading and array configuration. The PV system exhibits a non-linear I-V characteristic and its unique maximum power point on the P-V curve varies with insolation and temperature. The passing clouds, neighbouring buildings and trees are shadowing the PV arrays completely or partially as a result, it becomes more complex P-V characteristics with multiple peaks in case of partially shaded conditions. Conventional Maximum Power Point Tracking (MPPT) techniques fail to reach global peak power point and tend to stay in local peak power point which significantly reduces the efficiency of the PV system. This paper mainly focuses on extracting the maximum power from PV array under partially shaded conditions by executing improved hill climbing algorithm to identify the global maximum power point (GMPP) and SEPIC is used as a dc-dc interface. Simulation results have been presented to verify the performance of the proposed GMPPT technique.